Occurrence of alexithymia in patients with type 2 diabetes mellitus, arterial hypertension and their combination - I. E. Sapozhnikova (Лечащий Врач, 2022)
The objective is to study occurrence of alexithymia in patients with type 2 diabetes mellitus (DM-2), arterial hypertension (AH) and their combination. 3 groups of patients have been examined. Group 1 included 25 patients having DM 2 without AH (55 {51; 59} y.o., 7 (28%) men); group 2 included 25 patients of the same age and gender having DM-2 combined with AH; group 3 included 25 patients having AH and normoglycemia (57 {48; 62} y.o., 7 (28%) men). A number of evaluations have been done, such as a survey based on Toronto Alexithymia Scale (TAS-26), clinical and laboratory studies. The patients in all the 3 groups had a similar age, level of education and the number of working people didn’t differ. The patients in groups 1 and 2 received the same therapy for DM-2, level of glycosylated hemoglobin and incidence of DM-related chronic complications proved similar in these groups. High-grade alexithymia was detected in 14 (56%) patients in group 1, in 12 (48%) patients in group 2 (summary 52% patients with DM-2), in 9 (36%) patients in group 3. Group 3 showed absence of alexithymia (score TAS-26 < 62) more often (10 (40%)) as compared with groups 1 and 2 (3 (12%) patients in each group; χ2 1-3, р = 0,02). A higher score according to TAS-26 was detected in patients having DM-2 (group 1 + group 2) as compared having AH and normoglycemia (74 {69; 79} vs 69 {59; 74}, Mann – Whitney T-test, р = 0,022). 26 (52%) patients with DM-2 were detected to have high-grade alexithymia, while its occurrence was not connected to the presence of AH. Comparing with the patients having AH and normoglycemia, the patients with DM-2 more rarely showed the absence of alexithymia; the latter also had the higher score TAS-26.